Placental vascular tree characterization based on ex-vivo MRI with a potential application for placental insufficiency assessment. (November 2020) - Link, Daphna; Many, Ariel; Ben Sira, Liat; Tarrasch, Ricardo; Bak, Stella; Kidron, Debora; Gordon, Zoya; Yagel, Simcha; Harel, Shaul; Ben Bashat, Dafna
Abstract: Introduction: Understanding regarding the whole placental vascular network structure is limited. Our aim was to quantitatively characterize the human placental vascular tree ex-vivo using high-resolution MRI. Methods: 34 normal placentas were rinsed and injected with a solution of gelatin and contrast agent through the umbilical vessels. A sample of six placentas taken from pregnancies with intrauterine-growth-restriction (IUGR) was used to demonstrate the potential application to cases with placental insufficiency. Structural ex-vivo MR scans of the placenta were performed using high resolution T1 weighted images. A semi-automatic method was developed to segment and characterize the placental vascular architecture: placental volume and cord insertion location; number of bifurcations, generations and vessels diameters. Results: Different vascular patterns were found in placentas with central versus marginal cord-insertion. Based on the placental volume and number of bifurcations we were able to predict birth weight. Furthermore, preliminary results on IUGR sample demonstrated the potential of this method to differentiate between small newborns with suspected IUGR from small normal newborns who reached their full growth potential. Results obtained using the automatic method were validated against manual values demonstrating no significant differences or bias. Histopathology supported the imaging findings. Discussion: This is the first study to quantitatively characterize the human placental vascular architecture using high resolution ex-vivo MRI. Different patterns of vascular architecture may be related to different functioning of the placenta and affect fetal development. This method is simple, relatively fast, provides detailed information of the placental vascular architecture, and may have important clinical applications.